2016
DOI: 10.1134/s106377371607001x
|View full text |Cite
|
Sign up to set email alerts
|

X-ray variability of SS 433: Evidence for supercritical accretion

Abstract: We study the X-ray variability of SS 433 based on data from the ASCA observatory and the MAXI and RXTE/ASM monitoring missions. Based on the ASCA data, we have constructed the power spectrum of SS 433 in the frequency range from 10 −6 to 0.1 Hz, which confirms the presence of a flat portion (flat-topped noise) in the spectrum at frequencies 3 × 10 −5 − 10 −3 Hz. The periodic variability (precession, nutation, eclipses) begins to dominate significantly over the stochastic variability at lower frequencies, which… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…A similar model was proposed to explain the 164 d jet precession timescale of SS433 (Sarazin et al 1980;Katz 1981). Superorbital periods in the range of tens of days to 100 d, which could be attributed to precession 19 , have been observed in several ULXs (e.g., Mioduszewski et al 2004;Grisé et al 2013;Atapin & Fabrika 2016;Luangtip et al 2016;Brightman et al 2019Brightman et al , 2020Vasilopoulos et al 2020; see Weng & Feng 2018 for a systematic search with Swift observatory).…”
Section: Periodicitymentioning
confidence: 91%
See 1 more Smart Citation
“…A similar model was proposed to explain the 164 d jet precession timescale of SS433 (Sarazin et al 1980;Katz 1981). Superorbital periods in the range of tens of days to 100 d, which could be attributed to precession 19 , have been observed in several ULXs (e.g., Mioduszewski et al 2004;Grisé et al 2013;Atapin & Fabrika 2016;Luangtip et al 2016;Brightman et al 2019Brightman et al , 2020Vasilopoulos et al 2020; see Weng & Feng 2018 for a systematic search with Swift observatory).…”
Section: Periodicitymentioning
confidence: 91%
“…SS433 in fact exhibits X-ray emission with evidence for precession in the light curve(Atapin & Fabrika 2016), which are believed to arise from the jet rather than the accretion disk.16 Making such systems stable also reduces the predicted rate of binary BH mergers from population synthesis models, bringing them into better accord with observations by LIGO/Virgo.…”
mentioning
confidence: 99%
“…However, continued monitoring revealed that the modulation phase changed by 0.4 after a major outburst and was interpreted as evidence in favor of a superorbital origin (Pasham & Strohmayer 2013a). However, the phase of the X-ray minima of the 13 day orbital modulation of SS 433 is known to depend on the 162 day precession period of the jets (Atapin & Fabrika 2016), hence the orbital interpretation is not excluded.…”
Section: Long-term Periodicities and Quasi-periodicitiesmentioning
confidence: 99%
“…Examining the fast X-ray variability of SS 433 (Revnivtsev et al 2006), it has been found that its power density spectrum is well-fitted by a broken power-law with a flat component (P ∝ f 0 ) below 10 −3 Hz (Atapin et al 2015;Atapin & Fabrika 2016). This type of variability is similar to the flat-topped noise (hereafter FTN) observed in BHBs at the state of low accretion rate, i.e.…”
Section: Introductionmentioning
confidence: 54%
“…The linear rms-flux relation is observed in binary systems with black holes and neutron stars (Uttley & McHardy 2001;Gleissner et al 2004;Uttley 2004), active galactic nuclei (Vaughan et al 2003b gests that this mechanism must work in these systems as well. Moreover, the Lyubarskii's model was successfully applied to the variability of the supercritical accretion disc of SS 433 (Revnivtsev et al 2006;Atapin et al 2015;Atapin & Fabrika 2016).…”
Section: Lyubarskii's Proposalmentioning
confidence: 99%